On the Behaviour of Solutions of Xenon in Liquid Cycloalkanes: Solubility of Xenon in Cyclopentane - Bonifácio, Rui P. M. F. (2011)
The solubility of xenon in liquid cyclopentane has been studied experimentally and theoretically. Measurements of the solubility of xenon in liquid cyclopentane are reported as a function of temperature from 254.60Kto 313.66 K. The imprecision of the experimental data is less than 0.3%. The thermodynamic functions of solvation of xenon in cyclopentane, such as the standard Gibbs energy, enthalpy, entropy and heat capacity of solvation, have been calculated from the temperature dependence of Henry’s law coefficients. The results provide further information about the differences between the xenon + cycloalkanes and the xenon + n-alkane interactions. In particular, interaction enthalpies between xenon and CH2 groups in nalkanes and cycloalkanes have been estimated and compared. Using a version of the soft-SAFT approach developed to model cyclic molecules, we were able to reproduce the experimental solubility for xenon in cyclopentane using simple Lorentz-Berthelot rules to describe the unlike interaction.